EFFECTIVENESS OF VARIATIVE APPROACHES IN DEVELOPING STUDENTS' CREATIVE ABILITIES - Husniddin TOJIEV (Scholar Express Journal, 2025)
This article examines the effectiveness of variational approaches in developing students' creative abilities. Variational approaches, through the use of various methods and techniques, increase students' abilities to be creative, solve problems, and generate new ideas. The study aims to determine the role of such approaches in developing students' creative thinking in the educational process. The results indicate the importance of variational approaches in increasing students' creative potential.
Keywords: education; variability; methodology